Factors Associated With Candida auris Colonization and Transmission in Skilled Nursing Facilities With Ventilator Units, New York, 2016–2018. (28th September 2020) - Rossow, John; Ostrowsky, Belinda; Adams, Eleanor; Greenko, Jane; McDonald, Robert; Vallabhaneni, Snigdha; Forsberg, Kaitlin; Perez, Stephen; Lucas, Todd; Alroy, Karen A; Jacobs Slifka, Kara; Walters, Maroya; et al.
Abstract: Background: Candida auris is an emerging, multidrug-resistant yeast that spreads in healthcare settings. People colonized with C. auris can transmit this pathogen and are at risk for invasive infections. New York State (NYS) has the largest US burden (>500 colonized and infected people); many colonized individuals are mechanically ventilated or have tracheostomy, and are residents of ventilator-capable skilled nursing facilities (vSNF). We evaluated the factors associated with C. auris colonization among vSNF residents to inform prevention interventions. Methods: During 2016–2018, the NYS Department of Health conducted point prevalence surveys (PPS) to detect C. auris colonization among residents of vSNFs. In a case-control investigation, we defined a case as C. auris colonization in a resident, and identified up to 4 residents with negative swabs during the same PPS as controls. We abstracted data from medical records on patient facility transfers, antimicrobial use, and medical history. Results: We included 60 cases and 218 controls identified from 6 vSNFs. After controlling for potential confounders, the following characteristics were associated with C. auris colonization: being on a ventilator (adjusted odds ratio [aOR], 5.9; 95% confidence interval [CI], 2.3–15.4), receiving carbapenem antibiotics in the prior 90 days (aOR, 3.5; 95% CI, 1.6–7.6), having ≥1 acute care hospital visit in the prior 6 months (aOR, 4.2; 95% CI, 1.9–9.6), and receiving systemic fluconazole in the prior 90 days (aOR, 6.0; 95% CI, 1.6–22.6). Conclusions: Targeted screening of patients in vSNFs with the above risk factors for C. auris can help identify colonized patients and facilitate the implementation of infection control measures. Antimicrobial stewardship may be an important factor in the prevention of C. auris colonization. Abstract : Candida auris colonization among ventilator-capable skilled nursing facility residents is associated with recent hospitalization and antibiotic use. Odds of colonization were similar for colonized patients' roommates and others on the same ward. Entire units should be considered at risk.